Ecological Perspective: The Role of English Teachers at Private Elite Elementary Schools - Dinar Martia Azizah (Universitas Pendidikan Ganesha, 2025)
Learning is viewed as an ecological system consisting of many components inside and outside classroom which interrelated and dependent on each other. The ecology in roles of teachers is a lens that shows that all elements are interconnected to help to understand their roles from a holistic perspective. Thus, the purpose of the study is to analyze how the ecological context shaped the role of teachers at a religion-based school and an inclusive school. In this research, a qualitative multiple-case study involving purposive cross-case comparison sampling technique was employed to select principals, English teachers, homeroom teachers, and students of two private elite elementary schools. Data can be obtained through observation, semi-structured interview, students open-ended questionnaire, and document analysis. The activities in data analysis are data condensation, data display, and conclusion drawing/verification. This study demonstrates that English teachers both at A and B Elementary Schools play the similar roles as controller, director, and facilitator. Different role showed by English teachers who are as manager and resource. In conclusion, teachers need to have self-adaptation abilities with the situation and learning condition to play their roles effectively.